Uji Waktu dan Ketebalan Sistem Sayat Tangkai Manggar Terhadap Produksi Air Nira Kelapa (Cocos nucifera) di Desa Pasar IV Namo Terasi Langkat - Sulardi Sulardi; Tharmizi Hakim; Muhammad Wasito; Muhammad Taupik (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2023)
The aim of the study was to determine the timing and thickness of the manggar flower stalk cutting on the production of coconut sap water produced by Pasar IV Namo Terasi Village, Sei Bingai District, Langkat Regency. This study used a randomized block design (RBD) with the first factor consisting of 2 levels, namely W1 (slashed in the morning) and W2 (slashed in the afternoon). The second factor consists of 5 levels including K1 (slice thickness 2.0 mm), K2 (slice thickness 4.0 mm), K3 (slice thickness 6.0 mm) K4 (slice thickness 8.0 mm) and K5 (slice thickness 10.0 mm and 3 test. Data analysis results show that the tapping time in the afternoon is better and the production is more than in the morning. While the thickness of the incision on the stem of the coconut flower manggar is the best at a thickness of 10 mm.